MERANCANG RPP INOVATIF DALAM PROGRAM MERDEKA BELAJAR PADA MGMP IPS SMP SE-KABUPATEN JEMBER - Sri Kantun; Dwi Herlindawati; Lisana Oktavisanti M (LPPM Universitas Bina Bangsa, 2021)
The design of the RPP in the “Merdeka Belajar” program simplifies the making of lesson plans on one sheet. The three core components of the lesson plan are learning objectives, learning activities, and assessments. Therefore, it is necessary to immediately take concrete and innovative steps be able to produce an innovative RPP that can implement the true and complete